The Potential of Using Partial Discharge Analysis for Condition Monitoring of Polymer Insulator - Giriantari, I.A.D. (IPTEK The Journal for Technology and Science, 2025)
Polymeric insulators are widely used now days due to some advantages such as compact design, light, handy and easy to install therefore less installation cost. However, polymeric insulator can be deteriorate by ageing process due to UV, severe weather, extreme temperature, humidity, and vandalism. Deterioration due to severe weather and vandalism are usually undetectable. There are many techniques have been introduced in order to detect the insulator condition, one of the technique is introduce here by using Partial Discharge analysis. Study has been done in High Voltage Lab of UNSW Australia in order to investigate the potential of using Partial Discharge Measurement technique to monitor the insulator condition. Continuous PD measurement by examining the PD patterns and behaviour of three different insulator materials that are subjected to high humidity and pollution in the small chamber has been done. PD measurement has done by utilizing Computer Discharge Analyser 3 (CDA3). PD pattern was studied and examined including its statistical distribution and its scatter plot. It was done to be able to identify the PD’s parameters that can be used for condition monitoring. Polymeric insulators were tested in clean and polluted condition. The PD signal analysis can be done in energized condition by using high frequency current transformer. The CDA3 results in particular the statistical distributions and the scatter plots have exhibited a good correlation to the change of insulator’s surface condition. PD’s statistical distributions have given quantitative data of insulator’s surface condition, whereas the scatter plots have given the qualitative data. In addition, it was also found that high frequency component of the PD’s signal spectrum occurred when the insulator’s surface has been damaged. This monitoring technique of polymeric insulator condition by using PD analysis has a great potential.